The LIBOR mechanism and related games - Christoph Diehl (Bielefeld University, Institute of Mathematical Economics (IMW), 2013)
The London InterBank Offered Rate (LIBOR) is the most important set of interest rate benchmarks. Recently there have been reports about systematic manipulation of the LIBOR. We thus investigate incentives and possibilities to rig the LIBOR or related statistics for quote submitting panel banks. Both reputation concerns and financial exposure to the index may lead to misrepresentation of borrowing costs. Even in the static model we consider, we show that incorrect quoting is the standard and honesty the exception. In particular, we can theoretically explain why the LIBOR quotes were too low during the financial crisis which started in 2007, when increasing panel bank sizes is helpful and why individual quotes should be published with delay. Moreover, we evaluate and compare the performance of different aggregators like the median, the trimmed average and the average.
urn:nbn:de:0070-pub-26741480
Keywords: 330; Interbankenmarkt; Manipulation; Bank; Informationsverhalten; Ökonomischer Anreiz; Spieltheorie; Welt